2016
DOI: 10.1136/archdischild-2015-309310
|View full text |Cite
|
Sign up to set email alerts
|

Work of breathing during CPAP and heated humidified high-flow nasal cannula

Abstract: In infants with evolving or established BPD, CPAP compared with HHFNC offered no significant advantage with regard to the WOB, degree of asynchrony or oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
3
23
0
Order By: Relevance
“…Our study suggests that this pressure-to-flow ratio results in a similar level of support during nCPAP and HFNC. This finding is in line with previous crossover studies assessing the effect of HFNC and nCPAP on work of breathing measured with an oesophageal balloon 12 14 15. These studies reported no differences in work of breathing when comparing different flow rates (2–8 L/min) during HFNC with nCPAP levels of 5–6 cmH 2 O.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study suggests that this pressure-to-flow ratio results in a similar level of support during nCPAP and HFNC. This finding is in line with previous crossover studies assessing the effect of HFNC and nCPAP on work of breathing measured with an oesophageal balloon 12 14 15. These studies reported no differences in work of breathing when comparing different flow rates (2–8 L/min) during HFNC with nCPAP levels of 5–6 cmH 2 O.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies have investigated the association between flow rate and intrapharyngeal or transoesophageal pressure, showing conflicting results 12–14. The effect of HFNC on work of breathing has been studied using an oesophageal balloon or pressure catheter and no differences between HFNC and nCPAP were reported 12 14 15. However, most of these studies included a relatively small number of infants and measured work of breathing only once for a short period of time (<15 min).…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized crossover studies have attempted to investigate the effects of NCPAP and HFNC on physiological parameters. These studies revealed no differences in heart and respiratory rate, FiO 2 levels, oxygen saturation, work of breathing, thoraco‐abdominal asynchrony, or electrical activity of the diaphragm . However, the studies included more mature infants clinically stable on NCPAP for several days at the time of the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its increasing popularity, data on the physiological effects of NHF remains limited. A number of studies have investigated the potential continuous distending pressure that NHF may deliver and its effect on work of breathing (WOB) …”
Section: Introductionmentioning
confidence: 99%